Changes in Cardiovascular Emergency Risk Perception, Preparedness, and Blood Pressure Following a Risk-Mitigation Educational Program in Postmenopausal Women: A One-Group Pretest–Posttest Study. - Murbiah (Journal of health research and technology, 2026)
Background: Cardiovascular disease remains a major cause of mortality in women, and the menopause transition is accompanied by adverse changes in cardiometabolic and vascular risk. In addition, women may experience under-recognition of cardiovascular symptoms and delays in seeking emergency care. Theory-based education may strengthen risk perception and preparedness for appropriate responses to cardiovascular warning signs. Objective: To evaluate changes in cardiovascular risk perception and emergency-response preparedness, as well as systolic and diastolic blood pressure, following a cardiovascular emergency risk-mitigation educational program among postmenopausal women. Methods: A one-group pretest–posttest study was conducted among 46 postmenopausal women residing at the Tresna Werdha Indralaya Nursing Home, Indonesia. Participants were recruited using purposive sampling. The intervention comprised four sessions addressing cardiovascular risk, recognition of warning signs, decision-making, and case-based emergency-response simulation. Outcomes were assessed before and after the program using the Cardiovascular Disease Risk Perception and Response Scale (CVD-RPRS) and blood-pressure measurement. Pre–post differences were analyzed using paired-samples t-tests with a two-sided significance level of 0.05. Results: Participants had a mean age of 72.61 ± 7.09 years (range 60–85 years). The mean CVD-RPRS score increased from 96.04 ± 2.51 to 101.02 ± 2.73 (mean change 4.98; p<0.001). Mean systolic blood pressure decreased from 157.35 ± 11.62 to 155.20 ± 11.13 mmHg (mean change −2.15 mmHg; p<0.001), while mean diastolic blood pressure decreased from 88.85 ± 6.51 to 86.80 ± 6.59 mmHg (mean change −2.04 mmHg; p<0.001). Conclusion: The educational program was associated with improved cardiovascular risk perception and emergency preparedness and with small short-term reductions in blood pressure. Because the study lacked a control group, these changes should not be interpreted as definitive causal effects. Controlled studies with longer follow-up are needed to confirm effectiveness and clinical relevance. Keywords: cardiovascular emergency; health education; postmenopausal women; risk perception; emergency preparedness; blood pressure